Finitude and eternity: mental companions of soulful aging? - Lang, Frieder R. (Journal of religion, spirituality & aging, 2023)
It is a well-known finding that perceived finitude plays a critical role in the process of aging. The current article addressed how perceptions of finitude and eternity contribute to a soulful aging experience. Infinity is introduced as a temporal concept involving endurance and everlasting existence of time that marks the opposite end of finitude of a human life. Eternity, in contrast, relates to a timeless concept going beyond time without beginning or ending characterized by omnipresence. While the soul reflects eternity, the aging experience pertains to finitude. I suggest that the experience of soulful aging requires an integrative balance between reflections and perceptions of eternity and finitude. This involves a reappraisal of personal finitude into one of the three possible perceptions of infinity, that is, one that views infinity as not including the self, one that views infinity in being commemorated, and one that construes infinity as a possible afterlife of a soul. Conversing personal finitude into perspectives of infinity and eternity may also contribute to positive outcomes in the process of aging.